New metabolic pathway for degradation of 2-nitrobenzoate by Arthrobacter sp. SPG - Arora, Pankaj K.; Sharma, Ashutosh (Frontiers in Microbiology, 2015)
Arthrobacter sp. SPG utilized 2-nitrobenzoate as its sole source of carbon and energy and degraded it with accumulation of stoichiometric amounts of nitrite ions. Salicylate and catechol were detected as metabolites of the 2-nitrobenzoate degradation using high performance liquid chromatography and gas chromatography-mass spectrometry. Enzyme activities for 2-nitrobenzoate-2-monooxygenase, salicylate hydroxylase, and catechol-1,2-dioxygenase were detected in the crude extracts of the 2-nitrobenzoate-induced cells of strain SPG. The 2-nitrobenzoate-monooxygenase activity resulted in formation of salicylate and nitrite from 2-nitrobenzoate whereas salicylate hydroxylase catalyzed the conversion of salicylate to catechol. The ring-cleaving enzyme, catechol-1,2-dioxygenase cleaved catechol to cis, cis-muconic acid. Cells of strain SPG were able to degrade 2-nitrobenzoate in sterile as well as non-sterile soil microcosms. The results of microcosm studies showed that strain SPG degraded more than 90% of 2-nitrobenzoate within 10-12 days. This study clearly shows that Arthrobacter sp. SPG degraded 2-nitrobenzoate via a new pathway with formation of salicylate and catechol as metabolites. Arthrobacter sp. SPG may be used for bioremediation of 2-nitrobenzoate-contaminated sites due to its ability to degrade 2-nitrobenzoate in soil.